Il paese dei balocchi. Variazione sul tema delle “regole del gioco”, tra diritto e letteratura - Corigliano, Fabio (Cultura giuridica e diritto vivente, 2021)
[The land of toys. Variation on the "rules of the game", between law and literature] Among constitutionalists, political scientists, political philosophers and of course philosophers of law, and now also in the context of common discourse, the "rules of the game" are those rules of coexistence corresponding to the background of norms and "practices" governing the common life of men. But what are the rules of the game? Or better: what is the affinity rule that would allow the juxtaposition between play and life in human society? This contribution tries to suggest an alternative elaboration of the practice of play starting from childhood play, through the reading of some classics of children's literature.